The Grain of the Gods. Production Chain and Circulation of the Cacao of the Government of Girón in the Internal Neogranadino Market 1770-1810 - Bedolla Acevedo, Jason Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The objective of this article is to give an account of the production of cacao in the Girón governorate and its circulation in the internal market of New Granada, in the late 18th and early 19th centuries. The aim is to reconstruct the commodity chain ofcacao, with the different necessary links for the creation of this commodity. The different phases necessary for the cultivation and preparation of cacao are described, as well as the necessary social and commercial relationships between merchants and farmers that allowed for both the financing and circulation of the crops. For the development of this work, testaments, and debt and payment records registered in the Girón notarial archive were reviewed, as well as the alcabala record books of the city and the trade guides located in the Nation’s General Archive. The comparison of notarial and fiscal sources allows for an account of the necessary relationships between local merchants and farmers, the magnitude of the cacao trade, and its importance within the local economy at the end of the colonial period.